Analisis Strategi Integrated Marketing Communication Uniqlo Dalam Meningkatkan Brand Awareness - Aziz, Naufal Abdul; Dewi, Liza Dwi Ratna (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The Public Relations (PR) strategy implemented by Uniqlo within the framework of Integrated Marketing Communication (IMC) can be effective in enhancing brand awareness amidst the intense competition in the global retail industry and changing consumer preferences, particularly among the younger generation. This study aims to analyze the Public Relations (PR) strategy employed by Uniqlo to increase brand awareness through the approach of Integrated Marketing Communication (IMC). This research adopts a qualitative approach with an interpretive paradigm to gain an in-depth understanding of Uniqlo's PR strategy in enhancing brand awareness through IMC. Data was collected through in-depth interviews, observations, and documentation to explore stakeholder perceptions and experiences regarding the effectiveness of the implemented PR strategy. Data analysis was conducted using thematic analysis, beginning with verbatim transcription, coding, and grouping data into major themes relevant to PR strategy elements, the use of IMC, and factors influencing brand awareness. Themes were interpreted by relating them to the theories of Public Relations (PR), IMC, and brand awareness. The validity of the findings was strengthened through data triangulation from various sources. Conclusions were drawn based on the emerging patterns to evaluate the effectiveness of Uniqlo's PR strategy. The findings indicate that the success of Uniqlo's Public Relations (PR) and Integrated Marketing Communication (IMC) strategies in increasing brand awareness is influenced by communication consistency, product quality, commitment to sustainability, and adaptability to market changes. These factors synergistically build a positive and relevant brand image in the eyes of consumers. By maintaining message consistency across various communication channels, Uniqlo has not only enhanced brand recognition but also solidified its position as the top choice for consumers who value quality, comfort, and social responsibility. Well-integrated PR and IMC strategies have strengthened Uniqlo's image as a brand that is not only sales-oriented but also committed to social values and sustainability, which are highly appreciated by modern consumers.